Torque and Drag Forces Problems in Highly Deviated Oil Well - Neamah, Hasan Ali; A.Alrazzaq, Ayad A.Alhaleem (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Excessive torque and drag can be critical limitation during drilling highly deviated oil wells. Using the modeling is regarded as an invaluable process to assist in well planning and to predict and prevent drilling problems. Identify which problems lead to excessive torque and drag to prevent cost losses and equipment damage. Proper modeling data is highly important for knowing and prediction hole problems may occur due to torque and drag and select the best method to avoid these problems related to well bore and drill string. In this study, Torque and drag well plan program from landmark worldwide programming group (Halliburton Company) used to identify hole problems.one deviated well in Zubair oil fields named, ZB-250 selected for analyses the effect of friction factor on torque and effective `tension of the drill string along well depth, moreover the effect of well bore problems such as; mud losses, accumulation of cutting bed in the well bore, stuck pipe, caving, sloughing, high torque and drag values on drill string components and well trajectory. Wells data which include hole section size, mud properties, well profile survey, casing string depth, rig specification, drill string components, drilling parameters like weight on bit, rotary speed and flow rate were used  to compare between planning and drilling stages for these wells and identify the reasons of difference between these stages. The results showed a difference for the drilling  phase and increasable in effective tension, torque, pick up and slack off drag, measured string weight, and possibility to occur the buckling if compare with planning phase. Wellbore instability, high friction factor, high tortuosity, high flow rate ,stuck pipe , excessive drag  spot, partial to total losses, increase of drilling parameters, hard formations and bad hole cleaning, all these factors yield to this difference between planning and actual phases. When drilling hole section 8.5", the main causes of varying were drilling fluid losses, high value of friction factor, stuck pipe and friction forces when the maximum torque was (16 to 20 klb-ft) and pick up weight (20-40 klb)